Foreing Trade Functions in the Countries of the Economic and Monetary Union - Isidro Frías; A. David Carballas (European Regional Science Association (ERSA), 2004)
In this paper we focus on the major determinants of exports and imports in the member states of EU-15, giving a special emphasis on those belonging to the Economic and Monetary Union. For this reason we drive a general picture on the evolution of exports and imports. We analyse also the evolution of export and import prices, as well as the average labour productivity. Finally we estimate foreign trade equations both for imports and exports using the Johansen methodology. Among the major findings we can mention that we can reject the no cointegration among the import and export variables in the EU countries.
Keywords: 330